A supplement to the revision of the Scirtes flavoguttatus species-group (Coleoptera: Scirtidae: Scirtinae) - Ruta, Rafał; Kiałka, Agata; Yoshitomi, Hiroyuki (Zootaxa, 2014)
New species of the Scirtes flavoguttatus species-group are described from SE Asia. Altogether 34 species are newly described, including Scirtes beccus sp. nov. (Malaysia), S. bocakorum sp. nov. (Indonesia), S. crockerensis sp. nov. (Malaysia), S. decorus sp. nov. (Malaysia), S. dumogensis sp. nov. (Indonesia), S. gunongmulensis sp. nov. (Malaysia), S. ishikawai sp. nov. (Vietnam), S. kinabalensis sp. nov. (Malaysia), S. kundasangensis sp. nov. (Malaysia), S. lambriensis sp. nov. (Indonesia), S. leuserensis sp. nov. (Indonesia), S. luteus sp. nov. (Malaysia), S. malaisei sp. nov. (Myanmar), S. melinauensis sp. nov. (Malaysia), S. noonadan sp. nov. (Philippines), S. pallicolor sp. nov. (Malaysia), S. penampangensis sp. nov. (Malaysia), S. phoupanensis sp. nov. (Laos), S. prodigiosus sp. nov. (Malaysia), S. punctatus sp. nov. (Philippines), S. quasibalehensis sp. nov. (Malaysia), S. ranauensis sp. nov. (Malaysia), S. sarawakensis sp. nov. (Malaysia), S. seblatensis sp. nov. (Indonesia), S. sibayensis sp. nov. (Indonesia), S. sibolangitensis sp. nov. (Indonesia), S. sulawesicus sp. nov. (Indonesia), S. sulcigeroides sp. nov. (Malaysia), S. talinisensis sp. nov. (Philippines), S. ulukimanisensis sp. nov. (Malaysia), S. velutinus sp. nov. (Malaysia), S. vietnamicus sp. nov. (Vietnam), S. wallacei sp. nov. (Indonesia), S. yangsinensis sp. nov. (Vietnam). New localities of six species are provided. An updated identification key, checklist and a summary of distributional data are included. Probability of the occurrence of the Scirtes flavoguttatus species-group was evaluated with an analysis in MaxEnt software. It is highly plausible that members of the group occur in most mountainous rainforests of SE Asia.